ANALISIS KESESUAIAN PENGGUNAAN LAHAN TAHUN 2022 TERHADAP RENCANA TATA RUANG WILAYAH KABUPATEN BOYOLALI - Saifuddin, Muhammad; Danardono, Danardono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Land use is defined as human intervention in natural and human-made resources with the aim of fulfilling spiritual and material needs. Land use is inseparable from the phenomenon of land use change. Boyolali District is certainly not exempt from the phenomenon of land use change. Land use conversion has an impact on the inconsistency between land use and its designated plan. This study aimed to analyze land use changes from 2011 to 2022 and assess the suitability of land use in 2022 with the spatial plan of Boyolali District. This study applied survey and spatial analysis methods. The overlay technique produces maps of land use changes and the suitability of land use in 2022 with the Rencana Tata Ruang Wilayah (RTRW = Regional Spatial Planning) of Boyolali District. The results of the research showed that Kabupaten Boyolali experienced a land use conversion of 210.74 km2. Kecamatan Juwangi had the largest change in land use, covering an area of 30.37 km2, while Kecamatan Banyudono had the smallest change of 1.05 km2. The suitability of land use in 2022 with the Rencana Tata Ruang Wilayah (RTRW = Regional Spatial Planning) of Boyolali District indicates a suitable class covering an area of 797.24 km2, while an unsuitable class covers an area of 297.15 km2.